Podniková strategie a konkurenční výhoda - Kohoutová, Martina (Univerzita Pardubice, 1999)
This article describes important and significant role of competitive strategy in company. The paper also deals with process of formation, exploitation and sterilization competitive advantage.
Keywords: podniky; podniková strategie; konkurenční strategie